Release Control of Nanomagnetic Particles in Water and Wastewater Treatment - Pourzamani, Hamidreza; Fadaei, Saeid; Mehdi Amin, Mohammad (Anuário do Instituto de Geociências, 2017)
The present study was targeted to use of nanomagnetic column to remove toluene from water and wastewater and decrease release of nanomagnetic particles in environment. Based on the design of experiments (DOE), 16 experiments were arranged at 4 levels with 4 factors. The results showed that optimum condition for toluene concentration, NM dose, contact time and pH were100 mg.L-1, 2000 mg.L-1, 14 min, and 8, respectively. Although the toluene removal percent in batch system (greater than 98%) was higher in comparison to continuous system (greater than 95%), mass percent of nanomagnetic particles release in continuous system (7.6%) was less than batch system (28.3%).The equilibrium data was nicely fitted to the Brunauer-Emmett-Teller (BET) models. Our results indicated that these magnetic nanoparticles have high efficiency in toluene removal and nanomagnetic column has the capacity to reduce nano particles release into the environment by 20.7% in comparison to batch system.